Pre-market version of a commercially available hearing instrument with a tinnitus sound generator: feasibility of evaluation in a clinical trial. - Sereda, Magdalena; Davies, Jeff; Hall, Deborah A. (Taylor & Francis, 2016)
OBJECTIVE: This report considers feasibility of conducting a UK trial of combination devices for tinnitus, using data from the study which evaluated different listener programmes available within the pre-market version of Oticon Alta with Tinnitus Sound Generator. DESIGN: Open and closed questions addressed the following feasibility issues: (1) Participant recruitment; (2) Device acceptability; (3) Programme preferences in different self-nominated listening situations; (4) Usability; (5) Compliance; (6) Adverse events. STUDY SAMPLE: Eight current combination hearing aid users (all males) aged between 62-72 years (mean age 67.25 years, SD = 3.8). RESULTS: All eight participants reported the physical aspects and noise options on the experimental device to be acceptable. Programmes with amplification and masking features were equally preferred over the basic amplification-only programme. Individual preferences for the different programme options varied widely, both across participants and across listening situations. CONCLUSIONS: A set of recommendations for future trials were formulated which calls for more "real world" trial design rather than tightly controlling the fitting procedure.